THE EFFORT IN SHAPING THE CHARACTER OF STUDENTS THROUGH EXTRACURRICULAR ACTIVITIES: A STUDY FROM THE EDUCATIONAL MANAGEMENT SCIENCE PERSPECTIVE - Siti Mar’atus Solehah; Arrohmatan Arrohmatan; Nurul Hidayati Murtafi’ah (Al Wildan: Jurnal Manajemen Pendidikan Islam, 2022)
This research aimed to describe efforts to build students' character through extracurricular activities in the perspective of educational management science at the Hidayatul Mubtadiien Islamic boarding school, Bauh Gunung Sari Sekampung Udik Village, East Lampung city, Indonesia with a descriptive qualitative approach. The focus of the study in this study is how efforts to build students' character through extracurricular activities in the perspective of educational management science and analyze the supporting and inhibiting factors of the organization's activities. This research is based on the results of observations, interviews, and documentation at the research site. The results of the study found that character building was planned in a work program and neatly structured work system, then arranged in a complete and measurable division of tasks based on careful consideration and meeting results, then the work program was carried out in earnest to achieve the target. Achievement and superior character of the students, this activity are also controlled through work evaluations in meetings and direct assessments during extracurricular activities. The supporting factors for the success of forming the character of students through extracurricular activities are the activeness of the student administrators and member students in implementing the program, the provision of prizes for those who are disciplined and achievers, the existence of punishments for those who violate the rules, and the paradigm of students who learn to prepare themselves to take part in society. The inhibiting factors for the success of forming the character of students through extracurricular activities are the lack of facilities and infrastructure, unequal distribution of groups, busyness of students outside of extracurricular activities and the lack of preparation of students in extracurricular activities.